Studies on Correlation and Path Coefficient Analysis in Hybrid Rice (Oryza sativa L.) for Yield and Quality Traits - Vennela, M.; Srinivas, B.; Reddy, V. Ram; Balram, N. (International Journal of Bio-resource and Stress Management, 2021)
The present investigation was carried out at Regional Agricultural Research Station, Polasa, Jagtial, Telangana state, India to study the correlation and path coefficient analysis towards yield, physical and chemical quality traits in 46 genotypes including two checks in Randomized Block Design with two replications during kharif, october, 2019. Association of yield and yield components and among grain yield characters makes us to understand their relationship towards selecting a high yielding and good quality varieties. The result from the study revealed that all the nineteen characters studied has shown a great range of variation for correlation and path analysis. The character association studies in this experiment revealed that the trait grain yield plant-1 had showed significant positive correlation with plant height, spikelet fertility, 1000 grain weight, milling %, hulling %, kernel length and kernel breadth whereas it showed negative and non-significant association with days to 50% flowering. The path analysis studies revealed that kernel length was the major contributor for grain yield plant-1 followed by plant height, spikelet fertility, number of grains per panicle, 1000 grain weight, milling %, gel consistency, amylose content and alkali spreading value. These characters showed direct positive effects for grain yield plant-1. From the study it can be concluded that the above characters can be used directly as the selection criteria in any rice yield improvement breeding programmes.